1990
DOI: 10.4039/ent1221247-11
|View full text |Cite
|
Sign up to set email alerts
|

USE OF STANDARD TEMPERATURE THRESHOLDS AND PHENOLOGICAL PREDICTION FOR THE EUROPEAN CORN BORER (OSTRINIA NUBILALIS HÜBNER) IN ALBERTA

Abstract: A degree-day model was developed for Alberta populations of Ostrinia nubilalis Hübner. Starting with overwintered fifth-instar larvae, the model calculates the temporal distribution of first- and second-instar larvae which are the stages most vulnerable to chemical suppression. Predictions from three alternative models were compared against field data from southern Alberta. Use of a standard 10°C growth threshold to calculate physiological time scales allowed predictions as accurate as those obtained using eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…The statistical relationship between peak numbers of egg masses per stalk and larvae per stalk is similar to the results from other studies on trapping European corn borer adults on corn (Sappington and Showers 1983;Kelker et al 1990;Palaniswamy et al 1990), where trapping adults is suggested as only a guideline for the initiation of egg mass surveying.…”
Section: Discussionsupporting
confidence: 86%
“…The statistical relationship between peak numbers of egg masses per stalk and larvae per stalk is similar to the results from other studies on trapping European corn borer adults on corn (Sappington and Showers 1983;Kelker et al 1990;Palaniswamy et al 1990), where trapping adults is suggested as only a guideline for the initiation of egg mass surveying.…”
Section: Discussionsupporting
confidence: 86%
“…1). Similarly, Kelker et al (1990) used a biofix date of March 1 to estimate degree day accumulations for various life stages of European cornborer, Ostrinia nubilalis (Hüb-ner) in Alberta, while Ayre and Lamb (1990) used a biofix date of April 1 when measuring the number of degree days accumulated to 50 % adult emergence for nine species of noctuid cutworms in Manitoba, although species varied in overwintering stage from egg to pupa.…”
Section: Methodsmentioning
confidence: 99%
“…min daily temp)/2 -LTT] with a LTT of 6°C. Next, we calculated degree days using the double sine model with a LTT of 6°C and an upper threshold temperature of 32°C (vertical cutoff) (see Kelker et al 1990, University of California Natural Resources' website, http://www.ipm.ucdavis.edu/WEATHER/ index.html). Our biofix date, the date when we began to accumulate degree days each year, was selected as March 1st, since prior to this date temperatures were too low for degree days to accumulate using either method of calculation.…”
Section: Methodsmentioning
confidence: 99%
“…A linear relationship has the advantage of simplicity and validity in most cases (Matteson and Decker ; Kelker et al. ). The variability in development has also been represented using different approaches (Gilbert et al.…”
Section: Introductionmentioning
confidence: 99%